Identifying and Introducing the Soils of Faryab Province - Moqimzai, Omid; Faizi, Ahmad Omid (Journal for Research in Applied Sciences and Biotechnology, 2023)
Soil is a natural body that is located on the surface of the earth and contains various mixtures of decomposed stone materials, minerals and decayed organic materials, which provides the right amount of water, air and minerals to plants. In short, it can be said that soil directly and indirectly plays an important role in improving the living conditions of living organisms. From the point of view of a farmer, soil is the place where plants grow, which is used by humans. According to an engineer, soil is a natural phenomenon on which all buildings are built. The purpose of conducting this research (identifying and introducing the soils of Faryab Province and determining the pH and its nature) was to inform the farmers about the soils of Faryab Province, and the nature of the soils of this province was introduced to them, and also the proper use of the soils. The research is citation and descriptive type; Then it was analyzed in the laboratory, and as a result of the laboratory analysis and interviews, it was found that the soils of Faryab Province are among the loamy soils and its nature is sandy loam, which is suitable for growing fertile plants.